2012
DOI: 10.1097/won.0b013e318259c441
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting the Quality of Life of People With an Ostomy in North America

Abstract: The combination of a regular contact with a WOC nurse and the use of a double-layer adhesive appliance led to a significant reduction in leakage and accessory use, improved skin condition, and significant improvement in health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 11 publications
1
45
0
2
Order By: Relevance
“…160-163 a recent study of 743 patients with long-term ostomies revealed that 61% of patients had objective evidence of peristomal skin problems, 28% were experiencing frequent leakage, and 87% were using various accessories to facilitate pouching their ostomy. 160 after care by an ostomy nurse, leakage, skin problems, and the use of accessories decreased significantly, and quality-of-life scores improved. 160 this study was limited by the fact that all patients were changed to a new pouching system, so the care of the ostomy nurse was not the only intervention.…”
Section: Evidence For the Value Of An Ostomy Nursementioning
confidence: 98%
See 1 more Smart Citation
“…160-163 a recent study of 743 patients with long-term ostomies revealed that 61% of patients had objective evidence of peristomal skin problems, 28% were experiencing frequent leakage, and 87% were using various accessories to facilitate pouching their ostomy. 160 after care by an ostomy nurse, leakage, skin problems, and the use of accessories decreased significantly, and quality-of-life scores improved. 160 this study was limited by the fact that all patients were changed to a new pouching system, so the care of the ostomy nurse was not the only intervention.…”
Section: Evidence For the Value Of An Ostomy Nursementioning
confidence: 98%
“…160 after care by an ostomy nurse, leakage, skin problems, and the use of accessories decreased significantly, and quality-of-life scores improved. 160 this study was limited by the fact that all patients were changed to a new pouching system, so the care of the ostomy nurse was not the only intervention.…”
Section: Evidence For the Value Of An Ostomy Nursementioning
confidence: 98%
“…The use of regular wound ostomy care nursing has been shown to be an effective strategy to help manage peristomal dermatitis and improve quality of life. In a study by Erwin-Toth et al, the use of regular wound ostomy care nursing visits significantly increased the patient's quality of life and reduced the rate of ostomy appliance leakage [50]. Unfortunately, only 13% of patients in that same study had regular consultation with a wound ostomy care nurse prior to enrollment in the study, indicating a need for better patient access to care and increased resource utilization.…”
Section: Medical Managementmentioning
confidence: 99%
“…Cowin and Redmond's (2012) study showed that leakage for those with PSH occurs across day and night time with similar frequency. Erwin-Toth, Thompson and Davis (2012) demonstrated that for all ostomists, leakage had the most impact on QOL scores. Experts think that the physical burden and awkwardness of the peristomal bulging exacerbates fatigue,…”
Section: Physical Costmentioning
confidence: 99%